New Approach in the Management of Vertical Root Fracture with the Help of Biodentine and CBCT - H. C. Baranwal; Nidhi Singh; Neeraj Kumar; Riya Garg; Jyoti Yadav; Richik Tripathi (Hindawi Limited, 2020)
Introduction. Vertical root fracture is a big challenge to dentists for its diagnosis and treatment. As the tooth presents poor prognosis, the most common treatment modality is extraction. One can save the tooth from extraction by the reconstruction of fracture fragments followed by intentional reimplantation. New treatment options have arrived for healing of the fracture site by hard tissue barrier formation with the help of bioceramic materials. Case Report. The present case report describes successful management of complete vertical root fracture of a maxillary left central incisor by trauma in a 35-year-old male with the help of Biodentine, a bonding agent, a fiber post, and dual-cure resin cement without tooth extraction, followed by all ceramic crowns. Up to two years of follow-up, there is no problem in the tooth, and radiographically, there is no radiolucency along the fracture line. Periodontal status and probing depth were within a normal physiological limit. Conclusion. Functional and aesthetic outcomes are achieved by combined therapy in the present case report.